Assuan, Ägypten. Epigraphik, Bau- und Nutzungsgeschichte des Klosters Deir Anba Hadra. Die Arbeiten des Jahres 2018 bis Juni 2019 - Bodenstein, Ralph (e-Forschungsberichte des DAI, 2019)
Dayr Anba Hadra, also known as Monastery of St. Simeon, is situated on the West bank of the Nile at Aswan, about 1 km inland on top of a sandstone ridge overlooking a wadi. Its foundation is connected to local traditions about Hatre, a hermit saint and bishop of Aswan in the later 4th century AD whose hermitage is said to have been located here. The project investigates the history of the monastic complex from its  beginnings in the 7th–8th century up to the latest evidence of Christian-Coptic, Christian-Arabic and Muslim visitors’ inscriptions in the Mamluk period. The project work started in 2013 and is now concluding its first stage, working towards the publication of results. Important components are a building-archaeological study of the church and the workshop complex, and a comprehensive documentation of the rich epigraphic evidence – both Coptic and Arabic – as well as the wall paintings.